The role of monocytes and macrophages in the progression of Alzheimer’s disease - Nie, Wenyi; Yue, Yingbin; Hu, Jingqing (Frontiers in Immunology, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by β-amyloid (Aβ) plaques, neurofibrillary tangles (NFTs), and neuroinflammation. Monocytes and macrophages, particularly microglia, play a dual role in AD pathogenesis. In the early stages, they delay disease progression by phagocytosing Aβ, but chronic activation leads to Aβ accumulation and exacerbated neuroinflammation. Monocyte chemoattractant protein 1 (MCP-1) is a key regulator in neuroinflammation, Aβ deposition, and tau pathology, making it a potential therapeutic target. Moreover, recent breakthroughs in fluid and imaging biomarkers and targeted immunomodulatory agents underscore the growing importance of early diagnostic and therapeutic interventions. This review explores the complex interplay between monocytes, macrophages, and AD pathology, highlighting their roles in neuroinflammation, Aβ metabolism, and tau phosphorylation. Understanding these mechanisms offers new insights into developing effective diagnostic biomarkers and therapeutic strategies for AD.